2018
DOI: 10.1038/s41592-018-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody immunostaining for correlated light and electron microscopy with preservation of ultrastructure

Abstract: Morphological and molecular characteristics determine the function of biological tissues. Attempts to combine immunofluorescence and electron microscopy invariably compromise the quality of the ultrastructure of tissue sections. We developed NATIVE, a correlated light and electron microscopy approach that preserves ultrastructure while showing the locations of multiple molecular moieties even deep within tissues. This technique allowed the large-scale 3D reconstruction of a volume of mouse hippocampal CA3 tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 23 publications
0
92
0
2
Order By: Relevance
“…The latter technical constraints also affect EM immunolabeling techniques [10][11][12][13] which may furthermore be complicated by limited epitope accessibility. The fully genetic iron storage protein ferritin generates contrast via its electron-dense iron core [14][15][16] , but its small size complicates differentiation of individual ferritin particles from cellular structures.…”
Section: Multi-coloredmentioning
confidence: 99%
“…The latter technical constraints also affect EM immunolabeling techniques [10][11][12][13] which may furthermore be complicated by limited epitope accessibility. The fully genetic iron storage protein ferritin generates contrast via its electron-dense iron core [14][15][16] , but its small size complicates differentiation of individual ferritin particles from cellular structures.…”
Section: Multi-coloredmentioning
confidence: 99%
“…It has been suggested that nAbs preferentially bind to target proteins via a convex paratope (Wurch et al, 2012), which could contribute to the inability of the nAbs against the targets with the exception of Homer1 to detect aldehyde-fixed and/or denatured target proteins. While nAbs have widespread use in binding to native protein, which enhances their utility as chaperones for crystallography , some generated against GFP and other proteins have been used as immunolabels for immunohistochemistry (Fang et al, 2018;Yamagata and Sanes, 2018) and immunoblots (Bruce and McNaughton, 2017) In summary, we have generated a series of validated nAbs against neuronal proteins selectively expressed in specific subcellular compartments in brain neurons. These nAbs represent a valuable toolbox of reagents available to the neuroscience community for diverse applications.…”
Section: Discussionmentioning
confidence: 99%
“…nAbs are ideally suited for use as intracellular antibodies (intrabodies) in living cells (Beghein et al, 2016;Bertier et al, 2017;Lafaye et al, 2009;Schumacher et al, 2018;Staus et al, 2014;Van Audenhove and Gettemans, 2016), as they fold efficiently and remain stable under a wide range of conditions, including the reducing cytoplasmic environment (Boldicke et al, 2005;Gahrtz and Conrad, 2009;Goenaga et al, 2007;Lynch et al, 2008). In addition to their potential utility as intrabodies, nAbs also have advantages as immunolabeling reagents, as their small size (≈1/10 of conventional IgG antibodies) improves penetration of the cell or tissue samples (Fang et al, 2018;Perruchini et al, 2009). Importantly, nAbs improve imaging resolution by reducing the distance between the immunolabeling signal and the target protein from the 10-20 nm obtained with conventional primary and secondary antibodies down to 2-4 nm (Beghein and Gettemans, 2017;Pleiner et al, 2015;Ries et al, 2012;Szymborska et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, sample penetration of full antibodies is a problem when staining thick biological samples such as tissues, biopsies or whole organisms 17,19 . For the optimal labelling of these thick samples, protocols have been established, but they are often laborious and require time-consuming incubations up to weeks 20 or artifact-prone epitope retrieval protocols 21 .…”
Section: Mainmentioning
confidence: 99%